Artificial Intelligence: igniting creativity in comms & media - Ramlan, Muhammad Azril Izuan; Ab Rashid, Faridah Hanem (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Artificial Intelligence (AI) evolves from pure code into a powerful creative partner in the world of communication and media. In Mass Communication, AI merges technology with human creativity, enabling new forms of storytelling and collaboration. In journalism, AI tools generate real-time, data-driven reports, allowing journalists to focus on narrative and expression. In Public Relations and advertising, AI reads social trends and sentiments, helping craft messages that resonate. Rather than replacing humans, AI supports and enhances creative processes. This shift marks a new era of co-creation. AI is no longer just smart, it’s also expressive.